The missing effect of human recombinant Bone Morphogenetic Proteins BMP-2 and BMP-7 in surgical treatment of aseptic forearm nonunion. Issue 4 (April 2016) - von Rüden, Christian; Morgenstern, Mario; Hierholzer, Christian; Hackl, Simon; Gradinger, Franz Ludwig; Woltmann, Alexander; Bühren, Volker; Friederichs, Jan
Abstract: Introduction: In this cohort study, the surgical revision concept of open compression plating and autologous bone grafting with and without additional application of BMP for treatment of aseptic ulna and/or radius shaft nonunion was evaluated. The purpose was to evaluate the clinical and radiological outcome, and to determine any difference in osseous healing, range of time between revision surgery and bone healing, and postoperative complications between the cohort groups. Patients and methods: Between 01/2005 and 03/2015, a prospective, randomised, controlled cohort study was performed in a Level I Trauma Centre. Forty-nine patients were treated with the diagnosis of aseptic diaphyseal ulnar and/or radial shaft nonunion using compression plating and autologous bone grafting. Additional biological augmentation using BMP-2 or BMP-7 was performed in 24 patients. Clinical and radiological follow-up was performed six weeks, three and six months after revision surgery in accordance to the system by Anderson. Results: The study group consisted of 38 men and 11 women with a median age of 44 years (range 19–77). Twenty-four out of 49 patients obtained compression plating either with autologous iliac crest bone grafting (11/24 patients) or cancellous bone grafting (13/24 patients) and additional application of BMP-2 (4/24 patients) or BMP-7 (20/24 patients). The remaining 25 patients did not receive any additional application of BMP, but autologous bone grafting. The median follow-up was 15 months (range 6–54 months). Forty-six out of 49 nonunion healed within 12 months after revision surgery with a median time to union of six months. The clinical outcome, as assessed using the system by Anderson, as well as osseous healing, duration of time interval between revision surgery and bone healing, and postoperative complications did not demonstrate significant differences between the cohort groups. Discussion: Atrophic/oligotrophic forearm nonunion healed irrespective of additional application of BMP combined with autologous bone grafting. For successful treatment, radical resection of fibrous nonunion tissue and internal compression plate fixation is required with the aim of achieving high degree of rigid stability. Also, correction of angular deformities, restoration of length, and precise axial alignment of the distal radio-ulnar joint are mandatory prerequisites to successfully achieve bone healing.